Different 3'-end processing produces two independently regulated mRNAs from a single H1 histone gene. - Cheng, G H (1989)
We describe the isolation of a mouse H1 histone gene that encodes two mRNA transcripts. One mRNA ends just beyond the coding region, near a highly conserved palindrome sequence typical of cell cycle-regulated histone genes. The level of this transcript is coupled to DNA replication. The second mRNA ends nearly 1 kilobase downstream near a polyadenylation signal. This mRNA is polyadenylylated, and its accumulation is not coupled to DNA replication. The two mRNAs are regulated independently and in some circumstances in opposite directions under several physiological conditions. The production of a polyadenylylated mRNA from an otherwise cell cycle-regulated histone gene may allow for continued synthesis of the histone protein when DNA synthesis ceases in nondividing cells.